2014
DOI: 10.1016/s0254-6272(14)60089-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese herbs combined with in vitro fertilization and embryo transplantation on infertility: a clinical randomized controlled trial

Abstract: Our findings indicate that Chinese herbs increase endometrial thickness, improve the quality of fertility and embryo, and promote embryonic nidation, thus enhancing the success rate of in vitro fertilization/intracytoplasmic sperm injection-embryo transplantation cycle. Using Chinese herbs improves the outcomes and safety of assisted reproductive technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Chinese herbs and acupuncture are adjuvant therapies used for patients undergoing IVF [116,117] . Accumulating data suggest that Chinese herbs increase endometrial thickness and improve embryo quality, which may benefit IVF treatment.…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
“…Chinese herbs and acupuncture are adjuvant therapies used for patients undergoing IVF [116,117] . Accumulating data suggest that Chinese herbs increase endometrial thickness and improve embryo quality, which may benefit IVF treatment.…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
“…As shown in Table 2, traditional herbal medicines have been used to treat female infertility [191]. Several reports have suggested that traditional herbal formulas and medicinal herbs successfully improve endometrial receptivity and might be an alternative option for improving the outcome of embryo implantation [192][193][194]. Many herbal formulas have been studied for enhancing the embryo implantation rate in animal studies and clinical study [195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213].…”
Section: Possible Role Of Autophagy On the Effect Of Medicinal Herbal Drugs As Embryo Implantation Enhancermentioning
confidence: 99%
“…However, it has been reported that CHM can increase endometrial thickness significantly, which is considered to favor conception. 7 CHM is broadly used for treating infertility, and clinical trials have been mostly positive, without ART or IVF. According to Ried, 8 40 randomized controlled trials (RCTs) involving 4247 women with infertility who were treated with CHM were reported in 2015; CHM improved pregnancy rates significantly, compared to drug therapy, boosting pregnancy rates from 30% to 60% over 3-6 months.…”
Section: Introductionmentioning
confidence: 99%